A Design Methodology for an IoT-Enabled Warehouse Monitoring System in Pharmaceutical Storage Environments (Comprehensive Journal of Science, 2025)
In modern logistics, the Internet of Things (IoT) plays a vital role in enforcing Good Manufacturing Practices (GMP) by enabling precise environmental monitoring. Maintaining good storage conditions is essential for product safety. This research introduces a practical design and implementation of an IoT monitoring system in a pharmaceutical warehouse. The system uses sensors connected through Wi-Fi and Ethernet to monitor cold and ambient areas. It enables real-time tracking, automatic logging, and timely alarm notifications. The pilot system is designed, validated and testing confirms accurate sensor readings, reliable alarm delivery, and uninterrupted system performance during power and Wi-Fi outages. The system also supports remote access and interactive staff training. Results show that IoT integration offers a scalable, cost-effective approach to environmental monitoring, particularly for resource-limited sectors
Keywords: Internet of Things; Good Manufacturing Practices; Real-Time.